Analysis and Experimental Study on the Internal Flow Performance of Deep-Sea Biological Pumping Sampler - Guangping Liu; Yongping Jin; Youduo Peng; Deshun Liu; Buyan Wan (Chinese Journal of Mechanical Engineering)
Abstract To accurately acquire deep-sea live biological samples, a hydraulic suction macro-biological pressure-retaining sampler (HSMPS) was designed to achieve active capture of seafloor biological by a suction pump. The complex flow fields of deep-sea biologicals at three different locations were simulated. The deep-sea biologicals cause the flow field pressure and velocity to rise at different locations of the sampler, and the magnitude of the rise varies at different locations. The internal flow properties of the sampler were analyzed for different pumping flow rates the sampler. When the flow rate of the sampler pump was greater than 14 m3/h, the velocity of the inlet of the inflow area was greater than the limiting velocity of the deep-sea biologicals. The pumping test of deep-sea biologicals pumping sampler was carried out in the laboratory, and the test results were basically consistent with the simulation analysis. In order to balance the deep-sea biologicals damage and escape rate, the pumping flow of the sampler should be controlled between 14 and 16 m3/h. The test results provide a theoretical basis for the design of deep-sea biologicals sampling equipment.